Advanced IR sensing technology researchings in the city of Tomsk, USSR; Thermosense XII, Orlando, FL, United States, April 20, 1990 - Vavilov V. P. Vladimir Platonovich; Ivanov A. I.; Isakov A. V.; Reino V. V.; Shiryaev V. V. Vladimir Vasilyevich; Tsvyk V. V. Ruvim S. (1990, 1990)
Title screen